Analysis of Three DNA Barcoding (matK, rbcL, ITS) in the Anacardiaceae Family - Ningrum, Olivi Aruanda; Roslim, Dewi Indriyani; Herman, Herman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Anacardiaceae family is a group of tropical plants that have important economic value, but the identification of its species is often hampered by morphological similarities. Molecular approaches through DNA barcoding are an alternative to improve the accuracy of identification and kinship analysis. The purpose of this study was to analyze the combination of three DNA barcodes, namely (matK, rbcL and ITS) in the Anacardiaceae family. The materials used in this study were DNA sequence databases (rbcL, matK, ITS) from the Anacardiaceae family consisting of eight genera and one outgroup used, namely Pometia pinnata, downloaded from GenBank through the NCBI website. Sequences were aligned using MAFFT v.7, edited using BioEdit v.7.2, and analyzed using MEGA 11 to calculate nucleotide frequencies, nucleotide base pairs, diversity, and phylogenetic tree reconstruction using the Neighbor-joining method with 1000 bootstrapping times. The results showed that the matK sequence, a combination of matK+rbcL sequences, and a combination of matK+rbcL+ITS sequences were the most optimal barcodes for grouping species of the same genus in the Anacardiaceae family and separating out-group species. The ITS sequence, a combination of matK+ITS sequences, and a combination of rbcL+ITS sequences were able to group species of the same genus well but could not separate out-group species. The rbcL sequence was not optimal for use as a single DNA barcode.